Geometrical Optics Restricted Eavesdropping Analysis of Satellite-to-Satellite Secret Key Distillation - Ziwen Pan; Ivan B. Djordjevic (Entropy, 2021)
Traditionally, the study of quantum key distribution (QKD) assumes an omnipotent eavesdropper that is only limited by the laws of physics. However, this is not the case for specific application scenarios such as the QKD over a free-space link. In this invited paper, we introduce the geometrical optics restricted eavesdropping model for secret key distillation security analysis and apply to a few scenarios common in satellite-to-satellite applications.